ANALISIS DAMPAK PINJAMAN PERMODALAN NASIONAL MADANI (PNM) MEKAR SYARIAH TERHADAP KESEJAHTERAAN MASYARAKAT PRESPEKTIF HUKUM EKONOMI SYARIAH - Syamsinar; Lawang, Hasanna; Akil, M; Bunyamin, Andi; Raehana, Syarifa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the distribution mechanism and effectiveness of loans from PNM Mekaar Syariah, South Bontonompo Branch, Gowa Regency, in improving the economic welfare of the community in Pa'bundukang Village, South Bontonompo District, and to identify factors that influence the success of customers' micro-enterprises. The results of this study are expected to provide theoretical benefits as a reference in the development of Islamic economics, particularly related to microfinance-based poverty alleviation efforts, as well as practical benefits for PNM Mekaar Syariah in improving the quality of services and empowerment programs. The research method used is a qualitative approach with data collection techniques through direct observation, in-depth interviews, and documentation. Research informants consisted of active customers of PNM Mekaar Syariah and program managers. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions to obtain a valid picture of changes in the economic and social conditions of the community before and after receiving financing. The results of the study indicate that capital loans from PNM Mekaar Syariah have a significant impact on improving community welfare. Economically, customers are able to develop businesses and increase household income. Socially, group-based financing encourages discipline and responsibility. However, there were challenges in repaying installments when business declined. Overall, this program has proven effective in supporting Sharia-based community economic empowerment.